Amyloid Burden Is Associated With Self-Reported Sleep In Non-Demented Late Middle-Aged Adults - Sprecher, Kate E. (Neurobiol Aging, 2015)
Midlife may be an ideal window for intervention in Alzheimer’s disease (AD). To determine whether sleep is associated with early signs of AD neuropathology (amyloid deposition) in late midlife, we imaged brain amyloid deposits using Positron Emission Tomography (PET) with [C-11]Pittsburgh Compound B (PiB), and assessed sleep with the Epworth Sleepiness Scale (ESS) and the Medical Outcomes Study (MOS) Sleep Scale in 98 cognitively healthy adults (aged 62.4 ± 5.7 years) from the Wisconsin Registry for Alzheimer’s Prevention. We used multiple regression to test the extent to which sleep scores predicted regional amyloid burden. Participants reporting less adequate sleep, more sleep problems and greater somnolence on the MOS had greater amyloid burden in AD-sensitive brain regions (angular gyrus, frontal medial orbital cortex, cingulate gyrus and precuneus). Amyloid was not associated with reported sleep amount, symptoms of sleep disordered breathing, trouble falling asleep or ESS. Poor sleep may be a risk factor for AD and a potential early marker of AD or target for preventative interventions in mid-life.